Study of carbonyl compounds in white wine production - Herzan, Jakub (Food Sci Nutr, 2020)
Carbonyl compounds, especially acetaldehyde in white wines which have a detrimental effect on the aroma and overall stability of wine, were studied.. Seven wine samples of Grüner Veltliner were produced of one input raw material of grapes, all with different dosage of SO(2). The sulfur dioxide was maintained at a fixed level during the maturation process and sampled at six months. The grapes were processed, fermented, aged for three months in stainless steel tanks, prepared for bottling, bottled, and then aged in the bottle. In the samples taken, the volume of acetaldehyde, pyruvate, 2‐oxoglutarate, diacetyl, and acetoin was determined by HPLC with diode array detection. Individual forms of SO(2) were determined by iodometric titration. The wine that was matured on the lees and without the addition of SO(2) (variant (0/0/0)) contained the lowest amount of all compounds measured. For example, the volume of acetaldehyde for this wine was 2.7 mg/L at the end of the experiment. The results of the sensory analysis showed that such wine could compete with wines with higher SO(2) content without any problems.